Is the proximal tubule the focus of tubulointerstitial fibrosis?. Issue 2 (February 2023) - Peng, Zhi; Wang, Hui; Zheng, Jiaoyun; Wang, Jie; Xiang, Yang; Liu, Chi; Ji, Ming; Liu, Huijun; Pan, Lang; Qin, Xiaoqun; Qu, Xiangping
Abstract: Tubulointerstitial fibrosis (TIF), a common end result of almost all progressive chronic kidney diseases (CKD), is also the best predictor of kidney survival. Almost all cells in the kidney are involved in the progression of TIF. Myofibroblasts, the primary producers of extracellular matrix, have previously received a great deal of attention; however, a large body of emerging evidence reveals that proximal tubule (PT) plays a central role in TIF progression. In response to injury, renal tubular epithelial cells (TECs) transform into inflammatory and fibroblastic cells, producing various bioactive molecules that drive interstitial inflammation and fibrosis. Here we reviewed the increasing evidence for the key role of the PT in promoting TIF in tubulointerstitial and glomerular injury and discussed the therapeutic targets and carrier systems involving the PT that holds particular promise for treating patients with fibrotic nephropathy.